2022
DOI: 10.1111/tbed.14570
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and phylogenetic analysis of lumpy skin disease virus strain of outbreak in Guangdong, China

Abstract: In August 2019, lumpy skin disease occurred for the first time in Xinjiang, China, and then quickly spread to many provinces in China. Here, the virus was isolated from the skin scabs of affected cattle during June 2020 in Guangdong, China. Virus isolation, transmission electron microscopy and polymerase chain reaction identified lumpy skin disease virus (LSDV) in the skin crusts of sick cattle. For the isolation of LSDV, the most sensitive cell line is primary cattle testicular (PCT) cells, while Vero cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…In contrast to infection with bovine herpesvirus-2, which results in pseudo-lumpy skin condition and induces syncytia and intranuclear inclusion bodies in cell culture, LSDV causes a distinctive cytopathic effect and intracytoplasmic inclusion bodies [9]. According to Wang et al [47], the most sensitive cell line for the isolation of LSDV, is primary cattle testicular (PCT) cells, while vero cells cannot be used for the isolation of this virus.…”
Section: Virus Isolationmentioning
confidence: 99%
“…In contrast to infection with bovine herpesvirus-2, which results in pseudo-lumpy skin condition and induces syncytia and intranuclear inclusion bodies in cell culture, LSDV causes a distinctive cytopathic effect and intracytoplasmic inclusion bodies [9]. According to Wang et al [47], the most sensitive cell line for the isolation of LSDV, is primary cattle testicular (PCT) cells, while vero cells cannot be used for the isolation of this virus.…”
Section: Virus Isolationmentioning
confidence: 99%
“…It also can multiply in Madin-Darby bovine kidney cells and baby hamster kidney cells (BHK-21), but the pathological changes are slower. Recent investigations have found that LSDV can hardly proliferate in African green monkey kidney (Vero) cells ( Wang et al, 2022 ). Kumar et al (2021) treated Vero cells with the product of virus amplification from primary goat kidney (PGK) cells, and it could obtain higher viral titer only after adapting to LSDV and continuing to pass generations.…”
Section: Etiologymentioning
confidence: 99%
“…LSDV can proliferate on the chorioallantoic membrane of chicken embryo and cause acne-spots, and the virus does not cause the death of the embryo ( Black et al, 1986 ; Upton, 2004 ; Kumar et al, 2021 ). The next year, Chinese scientists found that LSDV could produce higher viral titers in primary cattle testicular cells ( Wang et al, 2022 ). When the wild-type virus was attenuated to prepare the vaccine strains, the state of the chicken embryo can be observed as a reference.…”
Section: Etiologymentioning
confidence: 99%
“…This indicates the presence of either multiple Capripoxviruses and/or novel recombinant viruses in this vaccine. Despite all the evidence for multiple new recombination events in LSDV, a single lineage has survived selection and established itself in southeast Asia ( Tran et al, 2021 ; Wang et al, 2022 ). Named after the first detection in China in 2019, the vast expansion of viruses belonging to this Chinese lineage, might be due to either enhanced viral fitness allowing domination over other genetic variants or because it spread into a susceptible cattle population in the absence of competing LSDVs.…”
Section: Poxvirus Recombinants In the Fieldmentioning
confidence: 99%